2022
DOI: 10.3389/fnins.2022.905979
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Cognitive Impairment After Mild Stroke: Connectomic Insights, Neuroimaging, and Knowledge Translation

Abstract: Contemporary stroke assessment protocols have a limited ability to detect vascular cognitive impairment (VCI), especially among those with subtle deficits. This lesser-involved categorization, termed mild stroke (MiS), can manifest compromised processing speed that negatively impacts cognition. From a neurorehabilitation perspective, research spanning neuroimaging, neuroinformatics, and cognitive neuroscience supports that processing speed is a valuable proxy for complex neurocognitive operations, insofar as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…At present, about two-thirds of patients with AIS only experience less neurological dysfunction during the acute phase 19 . Previous studies have shown that patients with MIS have a high incidence rate of PSCI 20 . Similarly, our study excluded patients with cognitive impairment prior to enrollment and found that the incidence of PSCI was also more than 50%.…”
Section: Discussionmentioning
confidence: 95%
“…At present, about two-thirds of patients with AIS only experience less neurological dysfunction during the acute phase 19 . Previous studies have shown that patients with MIS have a high incidence rate of PSCI 20 . Similarly, our study excluded patients with cognitive impairment prior to enrollment and found that the incidence of PSCI was also more than 50%.…”
Section: Discussionmentioning
confidence: 95%
“…“Neurocognition” is defined as a collection of interrelated domains such as executive function (EF), language and perceptual motor function, calculation, complex attention, memory, and visuoperception ( George et al, 2018 ; Holguin et al, 2022 ; RaukolaLindblom et al, 2022 ). Found that the Finnish KAT test is a valuable tool to detect cognitive-linguistic deficits by comparing the cognitive function of 48 adults with moderate to severe DAI and 27 healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…The Hopkins Language Learning Test (HVLT), Trail Making Test (TMT), and Rey–Osterrieth Complex Figure test were used to assess neuropsychological results in 25 DAI patients at 6 and 12 months post-traumatic, revealed that patients’ episodic verbal memory, attention, and executive function were improved at 6 and 12 months after the trauma ( Macruz et al, 2022 ). All of the above test methods could only evaluate certain domains of Neurocognition, and the Montreal Cognitive Assessment (MoCA) ( Nasreddine et al, 2005 ) was considered to be a more appropriate scale to comprehensively assess cognitive function after traumatic brain injury, subarachnoid hemorrhage, stroke and Alzheimer’s disease ( Cornea et al, 2022 ; Holguin et al, 2022 ; Wang et al, 2022 ). MoCA and resting-state perfusion magnetic resonance imaging were performed in 40 patients with acute mild TBI and 40 healthy controls within 14 days following injury to elucidate the relationship between cerebral blood flow connectivity differences and cognitive outcomes in the acute phase after mild TBI ( Duan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%